IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KOMPETENSI TENAGA PENDIDIK DAN KEPENDIDIKAN DI MI AL-AKBAR 1 DESA SIDOMULYO KECAMATAN AIR KUMBANG KABUPATEN BANYUASIN TAHUN AJARAN 2023/2024 - Siamsih, Esti; Adib, Abdul; Setyaningsih, Rina (UNISAN JURNAL, 2024)
This study aims to determine the Implementation of Human Resource Management in an effort to improve the competence of educators and education staff at the Imam Muslim Islamic Boarding School, Sei Rampah District, Serdang Bedagai Regency, North Sumatra Province. This research uses descriptive type qualitative research methods. The informants in this study were Education Personnel, Educators and students. Data collection techniques use observation, interviews, and documentation studies. Test the validity of data with increased persistence in research and using reference materials. Conclusions that can be drawn from the Implementation of Human Resource Management in an effort to improve the competence of educators and education staff at the Imam Muslim Islamic Boarding School, Sei Rampah District, Serdang Bedagai Regency, North Sumatra Province, have been implemented properly namely through resource management planning, implementation of human resource management and supervision and evaluation of human resource management.